STRATEGI ADAPTASI PETANI PADI ORGANIK DI ERA COVID-19 (Studi Kasus di Kelompok Tani Cidahu, Desa Mekarwangi Kecamatan Cisayong Kabupaten Tasikmalaya) - Devita Rusdianti; Yayat Sukayat (Universitas Galuh Ciamis, 2021)
Cidahu farmer group is a farmer group that started cultivating organic rice since 2005. Poktan Cidahu has a partnership with Gapoktan Simpatik as a formal institution that houses farmers in marketing organic rice production for domestic and export markets. Changes in demand from Simpatik Farmers Association to Farmers in the midst of the Covid-19 Pandemic led to several changes in farming activities and actions to fulfill the needs of farmer households. The purpose of this study is to describe the adaptation strategies carried out by organic rice farmers in the Covid-19 era. The research method used is qualitative with a case study approach in the Cidahu Farmer Group. Data collection techniques used are in-depth interviews, online interviews, observation, and documentation. Data analysis in this study used data collection techniques, data reduction, data presentation, and drawing conclusions. The results of this study indicate that farmers are making efforts to make adjustments to the changes caused by the Covid-19 Pandemic by implementing active, passive, network and field activity strategies. Based on this research, according to farmers, by implementing this strategy, they are able to minimize farmers from exceeding subsistence limits, be able to fulfill household needs and adapt to the situation amid the Covid-19 Pandemic.